2019
DOI: 10.1117/1.jbo.24.9.096003
|View full text |Cite
|
Sign up to set email alerts
|

Structured light imaging for breast-conserving surgery, part II: texture analysis and classification

Abstract: Subdiffuse spatial frequency domain imaging (sd-SFDI) data of 42 freshly excised, bread-loafed tumor resections from breast-conserving surgery (BCS) were evaluated using texture analysis and a machine learning framework for tissue classification. Resections contained 56 regions of interest (RoIs) determined by expert histopathological analysis. RoIs were coregistered with sd-SFDI data and sampled into ∼4 × 4 mm 2 subimage samples of confirmed and homogeneous histological categories. Sd-SFDI reflectance texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…It is during this transition, at n z = 10, ..., 40, where the introduction of finer details coincides with an improvement in classification performance for Fibrocystic Disease and Connective tissue, from ∼ 70% to ∼ 85% accuracy. In other words, performance improves as local structural variations surrounding a pixel is introduced and/or learned, to the point of allowing for individual identification, supporting parallel work that showed similar results on single-frequency, single-wavelength patch analysis [40]. It is important to note, however, that malignant tissue subtypes reach peak accuracy before higher-frequency texture is encoded in the keywords, suggesting the possibility of patient-specific spectral information that could be used in a case-by-case basis for margin delineation.…”
Section: The Role Of Texture In Classification Accuracysupporting
confidence: 59%
See 2 more Smart Citations
“…It is during this transition, at n z = 10, ..., 40, where the introduction of finer details coincides with an improvement in classification performance for Fibrocystic Disease and Connective tissue, from ∼ 70% to ∼ 85% accuracy. In other words, performance improves as local structural variations surrounding a pixel is introduced and/or learned, to the point of allowing for individual identification, supporting parallel work that showed similar results on single-frequency, single-wavelength patch analysis [40]. It is important to note, however, that malignant tissue subtypes reach peak accuracy before higher-frequency texture is encoded in the keywords, suggesting the possibility of patient-specific spectral information that could be used in a case-by-case basis for margin delineation.…”
Section: The Role Of Texture In Classification Accuracysupporting
confidence: 59%
“…By employing bottleneck clamping, it is possible to observe that average spectral properties can be explained with few dimensions, and that texture presents as low-variance, high-dimensional fluctuations that are embedded within spectral information. Furthermore, it can be concluded that pixel-wise optical properties are sufficient for identifying malignant tissue, but that the inclusion of local textural information helps to uniquely identify categories with prominent textural features, such as Fibrocystic Disease and connective tissue, as long as inter-patient variability is compensated, supporting work that analyzes textural information exclusively [40]. Moreover, the dataset shows a detectable superposition between connective tissue and malignant tissue subtypes in feature space, suggesting that the presence of collagen and elastin in malignant growths, recently observed in multiphoton microscopy [36], could perhaps be measured macroscopically; further research is needed to ascertain if such presence of connective tissue could be quantified.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Consequently, important textural information is omitted, which is considered in part II of this paper. 21 Textural information is known to be important in mammography. Its benefits occur at the pixel level because smaller regions can be included and allow the image analysis to retain its original spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Maloney et al used optical scattering analysis on SFDI data of 70 BCS specimens and demonstrated an extensive categorization of benign tissues into four types and malignant tissue into six types [85]. As scatter imaging involves long processing times and also susceptible to other sources of errors, the team investigated color analysis [85] and texture analysis [86] individually as a surrogate for the former. Both color and texture analyses enabled faster processing times but at the compromise of the categorization.…”
Section: Diffuse Optical Modalitiesmentioning
confidence: 99%